Novel Clinical and Laboratorial Challenges in Aspergillosis - Sabino, Raquel (2022)
In recent years, research in the areas of Aspergillus and aspergillosis has continued to ad vance rapidly, including advancements in genomics, immunological studies, clinical areas, and diag nostic areas. Recently, new risk groups for the development of aspergillosis have emerged—patients with influenza- or COVID-19-ssociated pulmonary aspergillosis. The rise and spread of antifungal re sistances have also become a clinical concern in some geographic areas and have drawn the attention of clinicians due to difficulties in treating these infections. In this paper, a snapshot of these issues is presented, emphasizing these novel clinical and laboratorial challenges in the aspergillosis field and focusing on their actual relevance.